Does corporate social responsibility affect mutual fund performance and flows? - El Ghoul, Sadok; Karoui, Aymen (Journal of Banking & Finance, 2017)
We use an asset-weighted composite corporate social responsibility (CSR) fund score to study the effects of CSR on fund performance and flows. Compared to low-CSR funds, high-CSR funds display poorer performance, stronger performance persistence, a weaker performance-flow relationship, and comparable persistence in flows. These findings are consistent with investors in high-CSR funds deriving utility from non-performance attributes.